Increased healthcare costs for filaggrin‐related eczema and asthma: hope for targeted management and prevention. (17th September 2018) - Akiyama, M.; Bray, N.
Abstract : Linked Article:  Soares et al. Br J Dermatol 2018;179 :717–723 .